УДОСКОНАЛЕННЯ КОНСТРУКЦІЇ КОТКІВ-УЩІЛЬНЮВАЧІВ ЛІСОСАДИЛЬНИХ МАШИН В КРИМУ - Agaponov, Mykola; Agaponov, Hennadyi (Наукові праці Лісівничої академії наук України, 2020)
The construction of making more compact skating rinks of forest-planting machine which are able to produce the high-quality sealing-off of root system of the planted plants on clay soils being in ripe (in crumbly) position only during few hours is grounded. The developed invention allows to improve to a great extent quality of planting of the plants and reduce his hauling resistance, because of making more compact skating rinks with the eccentrically located axes of rotation with the surface of soil co-operate not constantly. Thus probability of hammering their vegetable tailings and stone goes down substantially because jamming of root system of plants in a crack produced skating rinks cyclic (on a cycloid), that only in the places of placing of seedlings and nursery transplants.